Analisis Tingkat Literasi Keuangan Mahasiswa Perguruan Tinggi Negeri - Mohammad Alghein Syah (Jurnal Ilmu Manajemen, 2022)
This research aims to analyze the level of financial literacy of students of the Economic and Business Faculty. This research was designed as quantitative descriptive research. This research used a financial literacy test questionnaire to collect responses through purposive sampling. The result shows that the average financial literacy of students is in the high financial literacy category. Based on the outcome, students' financial literacy is influenced by parents' education. There is no significant influence of age and gender on students' financial literacy levels. Older students do not necessarily understand financial literacy, and younger students do not necessarily misunderstand financial literacy. Men and women students have the same perspective about financial literacy in this period. With this finding, students who receive or do not receive education or information about financial knowledge from their parents can dig deeper into financial concepts through formal and non-formal education, such as through universities, social media, and study group discussions. A high level of financial literacy can affect many social aspects of society, which are becoming more developed, and financial perspectives are becoming more modern.